Therapeutic efficacy of telitacicept in a patient with GFAP autoimmune astrocytopathy: a case report - Lin, Yan; Diao, Zengyan; Low, Jianwei; Wang, Aibin; Wu, Wei; Cao, Lili (Frontiers in Immunology, 2025)
Glial fibrillary acidic protein autoimmune astrocytopathy (GFAP-A) represents a rare form of autoimmune meningoencephalomyelitis, characterized by the presence of GFAP-IgG antibodies. In most cases, GFAP-A shows a dramatic response to high-dose corticosteroids, and escalation to additional immunotherapy is rarely required. Relapses occur in approximately 20–30% of patients, particularly in those with severe phenotypes such as myelitis or with concomitant malignancy. Here, we present a patient with GFAP-A who initially presented with Epstein–Barr virus (EBV) detected in the cerebrospinal fluid (CSF) but negative GFAP-IgG and was considered to have viral encephalitis. As the condition progressively worsened, repeat testing revealed CSF GFAP-IgG positivity (1:32) and serum positivity (1:100), confirming the diagnosis of GFAP-A. High-dose glucocorticoids and intravenous immunoglobulin (IVIG) produced only limited benefit. The patient presented with fever, meningoencephalitic symptoms, limb weakness, orthostatic hypotension, and MRI abnormalities involving the brainstem and cervical spinal cord. Given the suboptimal response, telitacicept (240 mg, subcutaneously weekly for four weeks, followed by biweekly administration), a dual BLyS/APRIL inhibitor targeting B-cell maturation and plasma cell survival, was initiated. Treatment resulted in rapid symptom resolution, marked radiological and CSF improvement, and stable remission during follow-up. No severe adverse events were observed. This case highlights telitacicept as a promising and well-tolerated therapeutic option for refractory GFAP-A.